Oxford Medicine Online 2016
DOI: 10.1093/med/9780198719410.003.0002
|View full text |Cite
|
Sign up to set email alerts
|

Consent and anaesthetic risk

Abstract: The incidences of mortality and morbidity associated with anaesthesia were reviewed. Most of the published incidences for common complications of anaesthesia vary considerably. Where possible, a realistic estimate of the incidence of each morbidity has been made, based on the best available data. Perception of risk and communication of anaesthetic risk to patients are discussed. The incidences of anaesthetic complications are compared with the relative risks of everyday events, using a community cluster logari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 127 publications
(157 reference statements)
0
11
1
Order By: Relevance
“…In particular, decreased duration of surgery leads to less time under general anesthesia and its associated complications. 11 We did not find a statistical significance in the rates of optimal debulking between the NACT and PS groups. In addition, although the number of dose reductions was not statistically significant, a P value of 0.056 suggests a possible relationship that could not be determined given the sample size.…”
Section: Discussioncontrasting
confidence: 60%
“…In particular, decreased duration of surgery leads to less time under general anesthesia and its associated complications. 11 We did not find a statistical significance in the rates of optimal debulking between the NACT and PS groups. In addition, although the number of dose reductions was not statistically significant, a P value of 0.056 suggests a possible relationship that could not be determined given the sample size.…”
Section: Discussioncontrasting
confidence: 60%
“…Our other five patients were medically fit to undergo GA, but opted to avoid GA. This decision making was likely to be influenced by awareness of the common adverse effects associated with GA, such as nausea, vomiting, disorientation and a slower recovery (22,23). Ultimately our findings have shown that with LA the breadth of the cohort suitable for SNS treatment is widened.…”
Section: Discussionmentioning
confidence: 87%
“…In their judgement in Montgomery, the Justices specifically warned against this approach but, more importantly, it cannot be regarded as good medical practice to expose all patients, irrespective of their needs or wishes, to a complex, long and potentially confusing list which many would find difficult to interpret. Others have described ways of quantifying risk in a more patient-friendly manner, and we would endorse these methods [2,3]. This does not mean that well-written patient information leaflets are not of help, of course, but they should be regarded as a background source of information informing a discussion, rather than as an end in themselves.…”
Section: A Maddockmentioning
confidence: 99%